A Web-Based Search Engine on Indigenous Plant for Medical Purposes - Khairulfitri@Khaironi, Nureen Izzati (IRC, 2020)
In today’s digital era there are rapid development of information technology such as search engine optimization (SEO) that very necessary among people to reach information through the Internet. This is because usually people use search engine for research purposes. People generally looking for an answer or information which to make decision and improve the knowledge. But if the search engine usability of a website is not a user friendly, the number of visits on the specific website will be lower. In fact, nowadays the existing biodiversity website about the indigenous plants are less exposed and known by most people. Plus, the existing biodiversity website usually provide information on common data such as the name of plant and the pictures but not for the usage. This may lead difficulty for users to find the information regarding the usage of the plants especially on medicinal purposes. Hence, the number of users visit on the exiting biodiversity website receive a little probability of attention. Therefore, the purpose of this study to improve the method of website search engine optimization of the proposed website in order to ease the users to retrieve information on indigenous plants especially for the medicinal purposes.